The Vague Position of the Dissertations in the Curriculum of the General Medical Doctorate Course - Yaghmaei, Minoo (Student Research in Translational Medicine, 2020)
Although in the general medical doctoral training program approved by the Ministry of Health and Medical Education in 2017, one of the professional duties of the graduates of this field is to participate in all educational and research activities approved by the competent authorities. However, in the main competencies and skills expected by the graduates of this field, there is no reference to research competencies (1). In this program, there are 293 credits, of which six are related to the dissertation. The study of this program shows that only the courses "Research Methods and Evidence-Based Medicine", "Medical Statistics", and "Principles of Epidemiology" are about how to conduct research, search for articles, basic principles of vital statistics, and types of studies (1). It is suggested that the following issues be considered before the next review of this program – Cont.